Identifying Sources and Oxidation of Methane in Standing Dead Trees in Freshwater Forested Wetlands - Martinez, Melinda; Ardón, Marcelo; Carmichael, Mary Jane (Frontiers in Environmental Science, 2022)
Wetlands are large sources of methane (CH4), therefore it is vital to understand the pathways, mechanisms, and sources to anticipate future positive feedbacks to climate change. Plant mediated transport of CH4 from sediment-borne gases is thought to be a major contributor in wetland ecosystems, though few studies have measured standing dead trees (snags). Snags are expected to become more common across the southeastern coast as marshes migrate into freshwater forested wetlands. In this study, our goal was to distinguish the main sources of CH4 being emitted from snags, that is, from soil or in situ origin. The δ2H and δ13C stable isotopic composition from various sources was sampled for source determination. We measured CH4 in various components: emissions from snag stem sides and the soil-atmosphere interface; and concentrations from snag trunk airspace at various heights from ground level (30, 60, and 120 cm), and soil porewater. Potential CH4 production and oxidation in tree cores from two heights (60 and 120 cm) was also measured to examine the potential for CH4 generation or oxidation in stems. We found that CH4 concentrations inside snags (~ 10-200 ppm) were 2-50 times higher than atmospheric levels, and generally decreased with increasing stem height. The stable isotopes δ13C and δ2H showed an enrichment from porewater to soils and snag stems. δ13C enrichment of CH4 in snag stems suggests that CH4 is being oxidized as it moves through snags. The tree core vial incubations showed that very few cores produced small amounts of CH4 under anaerobic conditions (n=5 out of 50), and very few cores oxidized CH4 under more aerobic conditions (n=5 out of 50). It is possible that a small amount of CH4 is produced in-situ within the heartwood, but it is likely this depends on the density, porosity, and aeration of snags (degree of decay). Our results highlight that high concentrations of CH4 can persist within the heartwood of snags long after initial decay, and that CH4 emitted from snags is largely derived from deep wetland soils and oxidized during transport (via diffusion) throughout the stem of snags.